Social Internet of Vehicles: Complexity, Adaptivity, Issues and Beyond - Siddiqa, Ayesha; Shah, Munam Ali; Khattak, Hasan Ali; Akhunzada, Adnan; Ali, Ihsan; Razak, Zaidi; Gani, Abdullah (Institute of Electrical and Electronics Engineers, 2018)
Social Internet of Things (SIoT) is a specialized form of adaptive networks, where any change in one node can affect other nodes in the network. Millions of devices, including vehicles, buildings, healthcare, industries, and several other types of devices, share and exchange sensitive data among each other. Interconnection of these devices changes the paradigms of the world around us and puts a great effect on the overall society. The number of nodes, types of devices, layout of the overall network, and sensitivity of the data adds more and more complexity in the domain of SIoT. In this paper, our contribution is twofold, first, we provide a brief and comprehensive overview of the social aspects of the IoT by selecting the most recent papers to investigate the complexity, adaptivity, and other social aspects of the IoT and their implications. The main aim of this paper is to analyze the benefits of IoT to the society, social acceptance of IoTs, and social connectivity of different age groups. Second, we forecast the future trends and predict the world in the year 2020. We provide a detailed analysis by using several different data tables to present the future trends of different aspects of SIoT. With this survey, we aim to provide an easy and concise view of different challenges in implementing SIoT and how it will affect the future smart cities and overall impact on the society.